Penggunaan Media Audio Visual Dalam Pembelajaran Daring Mata Pelajaran Bahasa Arab Di Sekolah Dasar Islam Terpadu Al-Halimiyah Jakarta Timur - Exa Miranda Moreri Razzaqi; Mujahidah Fharieza Rufaidah; Febri Priyoyudanto (Universitas Al Azhar Indonesia, 2022)
The Covid-19 pandemic has led to online learning in almost all schools in Indonesia, one of them being SDIT Al-Halimiyah, East Jakarta. This condition requires that every subject, such as Arabic, has innovation in the usage of learning media. Learning media are tools that function to clarify learning materials and help achieve better learning. One of the media that can support online learning is audio-visual media. The focus of the research discusses the online learning process, the use of audio-visual media for online learning, and the inhibiting and supporting factors for the usage of audio-visual media in online learning for Arabic language subjects. This study uses a qualitative approach with a descriptive method. The collection technique uses interviews and observations of Arabic teachers at SDIT Al-Halimiyah. Based on the results of this study, the researcher suggested that the online learning process used video materials made by the teachers, PowerPoint, voice notes, and online meetings. Learning videos are one of the audio-visual media most often used by teachers, and for difficult materials, students can ask the teacher through WhatsApp Groups, and Google Classroom. Audio-visual media is the optimal media in the online learning process. The supporting factors are subject matter that is easily accessible and repeatedly, makes it easier for teachers to convey material to many students, and learning materials are interestingly delivered. While, the inhibiting factors are unstable internet connections, the presence of students who did not have adequate electronic devices, and the lack of socialization of the use of audio-visual media from schools to teachers and students.Keywords - Covid-19, pembelajaran online, media audio-visual, mata pelajaran Bahasa Arab